Melacak Jejak Kebudayaan Nusantara, Membangun Semangat Ke - Bhineka Tunggal Ika – an - Puji Dwi Darmoko (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2018)
The forerunners of the ancestors of the Indonesian people are suspected as the descendants of a mixture of Mongolian, Caucasian and Negrito races, as humans with continental traditions, who then changed post-ice island archipelago traditions, long before BC in prehistoric times. Based on a University of Leeds study and published in May 2008, Molecular Biology and Evolution, most of the mitochondrial DNA lines (inherited by female offspring) have developed in the Southeast Asian island region for a longer period of time, namely since modern humans arrived around 50,000 years ago. The findings form the latest conclusions that refute the previous theory which states that there are multiple migration paths for Asian ancestors, namely through the northern and southern routes, and denied that the Southeast Asian people (who speak Austronesian languages) originated from Taiwan. This is evidenced by the development of maritime technology, the ancestors of the Indonesian people who were far more sophisticated than Europe at the same time, the cultural footprint of the inhabitants of the archipelago spread throughout the Indian Ocean region of the Netherlands and the Pacific, since Madagascar in the west, the Easter islands in the East, Hawaii in North, and New Zealand to the South. Outrigger known annually typical of the Archipelago, was found to spread throughout the Indian Ocean and Pacific Ocean regions. So if the clever scholars are able to feel the vibrations of the archipelago insight theory until the birth of the Republic of Indonesia with Unity in Diversity and Pancasila, Indonesian scholars must be able to examine more deeply about the specificity of the history and environment of the archipelago with maritime and agrarian souls, with dualism and dual diversity. single Fishya to be able to obtain the